FOCIS goes south: advances in translational and clinical immunology. (September 2017) - Kalergis, Alexis M; Anegon, Ignacio; González, Pablo A
FOCIS goes South: Advances in Translational and Clinical Immunology was the first Federation of Clinical Immunology Societies (FOCIS) (www.focisnet.org ) meeting held in Latin America (May 15–17, 2017, Santiago de Chile, Chile). The meeting was organized as a 3-day workshop and was fostered by the Millennium Institute on Immunology and Immunotherapy, a recently nominated FOCIS Center of Excellence. The workshop brought together FOCIS associates, such as members of the FOCIS Board of Directors, Directors of different Centers of Excellence, regional speakers and 350 attendees. The Meeting covered aspects of immune regulation and modulation, as well as immunotherapy in areas of autoimmunity, transplantation, cancer and infectious diseases, among others. The activity also had a full-day immunology course and a day-long flow cytometry course.